DEVELOPMENT OF SELF-COMPASSION SCALE INSTRUMENT FOR JUNIOR HIGH SCHOOL STUDENTS - Rakhmawati, Nur Fajrina; Suwarjo, Suwarjo; Eliasa, Eva Imania (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to develop an instrument in the form of a self-compassion scale for public junior high school students in Sleman Regency, Yogyakarta Special Region Province.Methodology – This study used the Research and Development (R&D) method. The scale's validity was assessed by three expert judgments consisting of Guidance and Counseling lecturers. The sampling technique for the reliability test used simple random sampling with a total sample of 32 public junior high school students in Sleman Regency. The instrument readability test involved 13 Guidance and Counseling teachers and five public junior high school students. The scale instrument was developed based on Neff's Self-Compassion theory, which consists of three dimensions: self-kindness vs self-judgment, common humanity vs isolation, and mindfulness vs over-identification. Content validity was measured by Aiken's Coefficient V, while reliability was tested using Cronbach's Alpha with the help of SPSS.Findings—The results of scale validation by three expert judgments showed an Aiken V index of 0.96 (highly valid). The scale's reliability based on Cronbach's Alpha was 0.88 (very high). The instrument's feasibility test showed that 100% of the statement items were feasible. In contrast, the readability test confirmed that the language in the instrument was appropriate for the age level of junior high school students.Significance—The self-compassion scale developed in this study proved valid and reliable, so it can be used as a measuring tool appropriate for the age development of junior high school students. This instrument is helpful for educators and practitioners in the field of Guidance and Counseling to measure and improve students' self-compassion in an educational context.Keywords: Self-compassion, Measurement scale, Validity, Reliability, Junior high school students